2017
DOI: 10.1002/ccd.27235
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐eluting stents versus coronary artery bypass grafting for left‐main coronary artery disease

Abstract: When compared with CABG, DES-PCI for LMCAD was associated with increases in RRV and the composite of death, MI, and RRV (with/without stroke), despite no differences in mortality, MI, stroke, and the composite of death and MI (with/without stroke).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…LM bifurcation lesions belong to a type of high-risk and complex lesions in coronary interventional therapy, and CABG is initially preferred for the treatment of LM bifurcation lesions. In recent years, in studies comparing CABG and PCI in the treatment of LM bifurcation lesions, it has been found that there is no difference between the two in clinical prognosis during long-term follow-up [3,4], and that PCI has a lower surgical risk in the treatment of the LM, but long-term follow-up shows a high angiographic restenosis rate, a high re-revascularization rate, and high incidence of cardiac death [12]. The development of the DES is a major breakthrough in the treatment of LM bifurcation lesions with PCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LM bifurcation lesions belong to a type of high-risk and complex lesions in coronary interventional therapy, and CABG is initially preferred for the treatment of LM bifurcation lesions. In recent years, in studies comparing CABG and PCI in the treatment of LM bifurcation lesions, it has been found that there is no difference between the two in clinical prognosis during long-term follow-up [3,4], and that PCI has a lower surgical risk in the treatment of the LM, but long-term follow-up shows a high angiographic restenosis rate, a high re-revascularization rate, and high incidence of cardiac death [12]. The development of the DES is a major breakthrough in the treatment of LM bifurcation lesions with PCI.…”
Section: Discussionmentioning
confidence: 99%
“…With the improvement of interventional techniques and stents, percutaneous coronary intervention (PCI) has proved feasible in the treatment of unprotected LM bifurcation lesions, and relevant studies have confirmed that there is no difference between PCI and CABG in the composite end point of death, cere brovascular accident, and myocardial infarction during treatment [3,4]. Therefore, PCI can be used as an effective and less invasive alternative to CABG.…”
Section: Introductionmentioning
confidence: 99%